STATUTORY RENEGOTIATION: A CRITIQUE. - Osborn, Richards C. (The Accounting Review, 1947)
Abstract The article presents a critical analysis of statutory renegotiation. Since it's inception in 1942, statutory renegotiation of the overall profits of contractors engaged in war business has been the subject of extended discussion. Business interests at first vilified but later grudgingly accepted renegotiation while government spokesmen in and out of the U.S. Congress have praised it most highly. Principal comments in the past have come from those who had an axe to grind on one edge or the other but it is now possible to evaluate critically the results of this legislation. Any evaluation of the accomplishments of renegotiation must first consider the background and intent of the Renegotiation Acts as well as the nature and scope of the avowed aims and then examine the degree to which these purposes have been fulfilled in actual practice. In the first World War, a major public scandal resulted from the excessive profits realized by corporations and individuals and as the production of war goods expanded in 1941, it became increasingly evident that tremendous profits would again be realized.